Indiana Jones and the last crusade [videorecording (Blu-Ray)] - Ford, Harrison, 1942-; Connery, Sean; Doody, Alison, 1966-; Spielberg, Steven, 1946- (Paramount, 2013)
Indiana Jones and his father go in search of the Holy Grail, battling Nazis along the way.